Holistic Approach in the Management of Kitibha Kushtha: A Case Study - godara, Saroj; Yadav, C R; Pratap Singh, Bhanu; Kohli, Ankita (International Research Journal of Ayurveda & Yoga, 2025)
Skin conditions can significantly impact both physical and emotional well-being, leading to a decreased quality of life. Factors such as altered lifestyles, lack of physical activity, poor hygiene, and mental stress commonly contribute to skin diseases. In Ayurveda, all skin disorders fall under the category of Kushtha, which is further divided into MahaKushtha and Kshudra Kushtha. Psoriasis, a chronic non-infectious inflammatory skin condition, characterized by well-defined red plaques covered with silvery scales. This condition is comparable to Kitibha in Ayurveda, as they share similar signs and symptoms. It is a subtype of Kshudra Kushtha primarily characterized by vitiated Vata and Kapha Dosha, exhibiting Shyava varnata, Kinvat Khara Sparsha, Parushata, and Kandu. The objective of this study is to evaluate the role of Shodhana Chikitsa in the management of Kitibha Kushtha. This case study highlights a 52-year-old male patient who visited the Kriya Sharir outpatient department at NIA Jaipur, presenting with skin lesions accompanied by intense itching on his upper and lower limbs, abdomen, and back. He was treated with Shodhana Chikitsa (body purification) using Virechana Karma. The patient experienced considerable relief from symptoms. The psoriasis area and severity index score also indicated notable improvements. Kitibha Kushtha can be effectively treated through the administration of shodhana therapy (virechan karma).